Recent Advances on the Function and Purification of Milk Exosomes: A Review - Li, Xiaoping; Su, Lan; Zhang, Xinling; Chen, Qi; Wang, Ying; Shen, Zhenwei; Zhong, Tian; Wang, Ling; Xiao, Ying; Feng, Xiao; Yu, Xi (Frontiers in Nutrition, 2022)
Exosomes are nano-scale extracellular vesicles, which can be used as drug carriers, tumor treatment, intestinal development and immune regulator. That is why it has great potential in pharmacy, functional foods, nutritional supplements, especially those for infants, postoperative patients, chemotherapy patients and the elderly. In addition, abnormal exosome level is also related to diseases such as cardiovascular diseases, tumor, diabetes, neurodegenerative and autoimmune diseases, as well as infectious diseases. Despite its high biological significance, pharmaceutical and nutritional value, the low abundancy of exosomes in milk is one of the bottlenecks restricting its in-depth research and real-life application. At present, there is no unified standard for the extraction of breast milk exosomes. Therefore, choosing the proper extraction method is very critical for its subsequent research and development. Based on this, this paper reviewed the purification techniques, the function and the possible applications of milk exosomes based on 111 latest references. Humble advices on future directions, prospects on new ideas and methods which are useful for the study of exosomes are proposed at the end of the paper as well.